DEVELOPMENT OF CREATIVE ABILITIES OF TECHNICAL UNIVERSITY STUDENTS - Makhynko, Valerii; Makhynko, Liudmyla (Sworld-Us Conference proceedings, 2023)
For its effective functioning, the modern industry requires highly qualified specialists who must possess not only technical skills in their speciality, but also have developed abilities for technical creativity. To meet these challenges, a modern technic